ANALISIS BUKU TEKS MATEMATIKA KELAS V SEKOLAH DASAR BERDASARKAN ASPEK ISI, PENYAJIAN, BAHASA, DAN GRAFIKA - Syalsabiluna, Syalwa; Rahmatul Nur Laely, Dinda; Nurlaila, Tsani; Umimah, Sovia; Fatonah, Siti; Nopasari, Dewi (Cahaya Ilmu Bangsa Institute, 2024)
Textbooks play a crucial role in the learning process, both for students as a source of learning materials and for teachers as a guide for teaching materials. This study aims to analyze a fifth-grade mathematics textbook written by Prof. Wono Setyo Budhi, Ph.D., and published by Erlangga. This research employs a literature review method, which involves collecting data by examining various written sources such as books. In this study, data was obtained by observing the fifth-grade mathematics textbook written by Prof. Wono Setyo Budhi, Ph.D., published by Erlangga, with a focus on analyzing its content validity, presentation, language, graphics, strengths, and weaknesses. The fifth-grade mathematics textbook by Prof. Wono Setyo Budhi, Ph.D., has been analyzed in this study, and the results show that the textbook generally meets curriculum standards and learning objectives. The material is presented in a simple, engaging, and relevant manner to everyday life, making it easy for students to understand and appropriate for their developmental level. This textbook provides material supplemented with various questions and exercises, such as stories, discussions, and project activities, to encourage students to actively engage in the learning process. The book is also equipped with scannable barcodes that link to educational videos, tables, graphs, and clear and attractive images, which can help students understand the material more easily, stay motivated in learning, and enhance their learning experience. However, there are several aspects that need improvement, such as the black-and-white illustration design and the lack of a glossary to facilitate understanding of new terms. Overall, this textbook can be a good reference for teachers and students in fifth-grade mathematics learning, but some visual details need to be improved to enhance its quality. Keyword: textbook, mathematics, class V, elementary school